AB1160 Epidemiology and clinical presentation of ocular involvement in a population of 278 patients with non infectious uveitis. (15th June 2017) - Venerito, V; Lopalco, G; Cantarini, L; Fabiani, C; Fornaro, M; Vitale, A; Guerriero, S; Favale, R; Giannini, M; Nivuori, M; Cacciapaglia, F; Laselva, G; et al.
Abstract : Background: Uveitis is a sight-threatening inflammation which may involve different anatomic parts inside the eye. Rheumatologists should be aware of the ocular clinical signs and of the frequency of uveitis because it may cause irreversible lesions to the eye that predominantly affect people in their most productive years, being one of the most common extra-articular manifestation in several rheumatic diseases. Objectives: We aimed to describe the presentation of the clinical features of ocular involvement in a population of patients affected with newly diagnosed Non Infectious Uveitis (NIU). Methods: 278 patients (mean age 42±18, 18 years, range 4 - 87) from three specialized centres, all affected with uveitides, were enrolled; 158 were female, 120 male, all caucasian but one asiatic. Complete ophtalmologic examination was carried out in all of them, malignancy or infections of any kind were preventively ruled out. In addition blood tests, serum antibodies level evaluation and HLA haplotype typization were performed. Moreover instrumental tests were performed when a relation with systemic diseases was suspected. Uveitides were then classified according to the Standardization of Uveitis Nomenclature Working Group Criteria. Results: 149 (53, 6%) patients were affected with Anterior Uveitis (AU), 45 (16, 2%) with Panuveitis, 16 (5, 8%) with Intermediate Uveitis (IU) and 68 (24, 5%) with Posterior Uveitis (PU). 110 (41, 7%) patients were known to have a systemic disease at the moment of the uveitis onset. HLA-B27 positivity was found in 15, 8% of patients, whereas HLA-B51 positivity was found in 21, 9% of patients. Behçet's Disease (BD) was diagnosed in 39 (14%) patients: in particular AU was found in 9 out of 39 patients (23, 1%), while PU in 16 out of 39 patients (41%). Ankylosing Spondylitis (AS) was recognized in 22 (7, 9%) patients: AU was diagnosed in 16 out of 22 (72, 7%) of them while 4 out of 22 (18, 2%) where affected with Panuveitis. The cases of Psoriatic Arthritis (PsA) were 9 (3, 2%); specifically, AU was recognized in 4 out of 9 (44, 4%) of them while PU was found in 5 out of 9 (55, 6%) of them. We also defined the most common form of uveitis in patients affected with either Juvenile Idiopathic Arthritis, or Systemic Lupus Erythematosus, or Sarcoidosis, or Vogt-Koyanagi-Harada disease or Inflammatory Bowel Diseases. The idiopathic form of uveitis, was diagnosed in 162 (58, 3%) patients. Anti-nuclear antibodies (ANA) levels were assessed in 148 patients of whom 57 (38, 5%) have been found ANA positive and 91 (61, 5%) ANA negative. Notably 38 (66, 7%) ANA positive patients were affected with AU. Conclusions: Our study provides a depiction of clinical features and epidemiology of ocular involvement in a huge population of patients presenting newly diagnosed NIU. Notably, in our population, idiopathic uveitis was the most commonly diagnosed form; it took shape of AU in 56, 6% of cases. The majority of HLA-B27 positive uveitides were also AU (68, 2%), while, among HLA-B51 uveitides, PU (39, 3%) and AU (37, 7%) were recognized as the most common presentations. Disclosure of Interest: None declared